Das Wurzelerweiterungsaffix ḥ im Ägyptischen (und im Afroasiatischen) - Brose, Marc (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Quite long known in the linguistic research of Ancient Egyptian is an affix ḥ which is used to augment both verbs and nouns, whereas the meaning of that affix could not be figured out in a convincing theory until today. This article gives an overview about the research history in Egyptian and Afroasiatic linguistics, makes an attempt to determine the basic meaning as plural-extensive with several specific nuances when the affix is joined to verbs, like factitive, resultative, adversative. It also discusses diverse theories about its existence in other branches of the Afroasiatic phylum and shows that the recent evidence in these branches is too little and / or too dubitable to postulate such an affix with comparable meaning like the Egyptian one. Otherwise, as it is shown, the Semitic branch has created patterns with similar value, the gemination patterns of the type qVttVl in several varieties and derivations.